Research on conflicts in Cai Lay district, Tien Giang province, between local residents and stakeholders in community-based tourism development - NGUYEN, Ngoc Anh; CHUNG, Khang Le (Edelweiss Applied Science and Technology, 2025)
The current research incorporates a qualitative approach to conduct in-depth interviews with 23 respondents, including 7 locals, 10 visitors, 2 employees of tourism-related businesses, and 4 government officials, in order to examine conflicts in the process of community-based tourism development in Cai Lay District, Tien Giang Province. The investigation essentially identifies three primary categories of conflict: environmental, social, and economic. Disproportionate benefit distribution is the fundamental root of economic conflicts; in the case of tourism, companies attempt to regulate both the flow of customers and profits, while local residents are provided with a restricted quantity of benefits. The sustainability of the community-based tourism model is threatened by the imbalanced competition between locals and business proprietors, as well as the unpredictability of taxi revenue. As a result of a lack of transparency in support policies, social conflicts arise between residents and the government regarding issues of disrespect, local culture, and historical inequality among tourist households. Environmental conflicts are frequently caused by tourists' detrimental effects, such as littering and businesses' overuse of resources, which degrade locals' quality of life. The study determines strategies to enhance cooperation between the relevant parties, guarantee equitable benefit distribution, and establish a framework for the long-term growth of community-based tourism in Cai Lay District.